Rahasia sukses belajar pada remaja: Mulailah dengan tidur yang cukup - Murti, Mitra Dwi (Maliki Interdisciplinary Journal, 2025)
Sleep is a basic biological need that is very important in maintaining physical and mental health. Research has shown that lack of sleep can trigger a variety of health problems, from impaired concentration to chronic disease. Factors such as excessive use of gadgets, stress, and changes in modern lifestyle often interfere with healthy sleep patterns. This article examines the importance of getting enough sleep, the negative impacts of lack of sleep, and various factors that influence sleep quality. Apart from that, this article also presents several practical solutions to overcome the problem of lack of sleep, such as maintaining a clean sleeping environment, setting a regular sleep schedule, and increasing physical activity.